Diverse Risk Preferences and Heterogeneous Expectations in an Asset Pricing Model - Thomas Gomez; Giulia Piccillo (Center for Economic Studies and ifo Institute (CESifo), 2019)
We propose a heuristic switching model of an asset market where the agents' choice of heuristic is consistent with their individual risk aversion. They choose between a fundamentalist and a trend-following rule to form expectations about the price of a risky asset. Given their risk aversion, agents make a deterministic trade-off between mean and variance both in choosing a forecasting heuristic and determining the number of risky assets to buy. Heterogeneous risk preferences can lead to diverse choices of heuristic. Using empirical estimates for the distribution of risk aversion, simulations show that the resulting time-varying heterogeneity of expectations can give rise to chaotic dynamics: irregular booms and busts in the asset price without exogenous shocks. Small, stochastic price shocks lead to larger asset price bubbles, and can make stable solutions explosive. We prove that a representative agent cannot capture our model.
Keywords: D81; D84; G11; G12; G41; 330; heterogeneous risk aversion; bounded rationality; heterogeneous expectations; heuristic switching; asset pricing